2019
DOI: 10.3390/nu11030496
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Components That May Influence the Disturbed Gut Microbiota in Chronic Kidney Disease

Abstract: Gut microbiota imbalance is common in patients with chronic kidney disease (CKD) and associates with factors such as increased circulating levels of gut-derived uremic toxins, inflammation, and oxidative stress, which are linked to cardiovascular disease and increased morbimortality. Different nutritional strategies have been proposed to modulate gut microbiota, and could potentially be used to reduce dysbiosis in CKD. Nutrients like proteins, fibers, probiotics, and synbiotics are important determinants of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(107 citation statements)
references
References 136 publications
(177 reference statements)
2
104
0
1
Order By: Relevance
“…Gut dysbiosis, which refers to alterations in the composition and function of the gut microbiota, has been attracting increasing attention due to its association with various diseases, including obesity, atherosclerosis, DM, cancer, and CKD [38]. Dietary components that escape digestion in the small intestine are fermented through metabolism by the gut microbiota.…”
Section: Gut Dysbiosismentioning
confidence: 99%
See 1 more Smart Citation
“…Gut dysbiosis, which refers to alterations in the composition and function of the gut microbiota, has been attracting increasing attention due to its association with various diseases, including obesity, atherosclerosis, DM, cancer, and CKD [38]. Dietary components that escape digestion in the small intestine are fermented through metabolism by the gut microbiota.…”
Section: Gut Dysbiosismentioning
confidence: 99%
“…The effects of these agents on the composition of the gut microbiota and gut-derived uremic toxins have been increasingly reported. Based on a meta-analysis by McFarlane et al [79], Mafra et al did not recommend probiotics as a sole intervention, but suggested an increased intake of foods with a high content of prebiotics in CKD patients [38]. Further studies are required to establish a more effective, sophisticated prescription of these agents.…”
Section: Probiotics Prebiotics and Synbioticsmentioning
confidence: 99%
“…The bioactive compounds in foods like polyphenols, and their potential to modulate intestinal microbiota, have been given more recent attention. These compounds, which are powerful antioxidants and natural anti-inflammatory agents, are widely used to prevent inflammation and oxidative stress in chronic "burden of lifestyle" illnesses (91). Several studies have confirmed the capacity of probiotics to control gastrointestinal disease, and the success of treating CKD patients with Clostridium difficile infection should be paid particular attention in this regard (79).…”
Section: Polyphenols Microbiota and Ckdmentioning
confidence: 99%
“…Therefore, raising similar questions about the effects of the intestinal microbiota on CKD (120) seems logical and reasonable. In comparison, the effects of food and nutraceuticals on the uremic phenotype and its contribution to intestinal dysbiosis, given the enormous capacity of food to be used as medicine for CKD, warrant much greater attention (91).…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…For a correction of human microbiota, it is often recommended to prescribe pro-, pre-or synbiotics. However, their use does not lead to a prevention of the NCD's due to a lack of probable criteria for assessing their efficacy in clinical trials and sporadic and non-personified use [18].…”
Section: Introductionmentioning
confidence: 99%